Validation of pain catastrophizing scale on breast cancer survivor - Pérez-Cruzado, David Francisco; Roldán-Jiménez, Cristina; Iglesias-Campos, Marcos; Pajares, Bella; Alba-Conejo, Emilio; Cuesta-Vargas, Antonio (Wiley, 2022)
Introduction: Pain catastrophizing scale (PCS) is the most used scale to measure pain catastrophizing. In breast cancer survivors (BCS), pain catastrophizing is related to upper-limbs dysfunction and disability. This study aimed to assess the internal consistency, internal structure, and convergent validity of the Spanish version of the PCS in Spanish BCS. Material and Methods: Breast cancer survivors were recruited from the service of Medical Oncology of the University Clinical Hospital Virgen de la Victoria, in Málaga (Spain). The psychometric properties were evaluated with analysis factor structure by maximum likelihood extraction (MLE), internal consistency, and construct validity by confirmatory factor analysis (CFA). Results: Factor structure was three-dimensional, and one item was removed due to cross-loading. The new 12-item PCS showed a high internal consistency for the total score (α = 0.91) and a good homogeneity, and CFA revealed a satisfactory fit. PCS showed an acceptable correlation with FACS (r =0.53, p <0.01). Conclusion: Pain catastrophizing scale is a valid and reliable instrument to evaluate pain catastrophizing in Spanish BCS. This tool may help clinicians in the management of pain by assessing pain and by measuring the effect of interventions.
Keywords: Mamas -- Cáncer; Breast cancer; Catastrophizing; Chronic pain; Psychometric properties; Validation studies